Diminished LC3 Expression with Unchanged Beclin 1 Levels in Right Atrial Appendage Tissue of Diabetic Patients Undergoing Coronary Artery Bypass Graft - Rajendran, Raji Sasikala; Jayakumari, Nandini Ravikumar; Pillai, Vivek Velayudhan; Karunakaran, Jayakumar; Gopala, Srinivas (Annals of the National Academy of Medical Sciences (India), 2023)
Type 2 diabetes potentiates the risk of heart failure. A vital physiologic process, autophagy, may be impaired in the diabetic heart. The aim of this study was to explore the autophagic status in a human diabetic heart. Techniques like immunohistochemistry and western blotting were employed to examine the expression of some of the important proteins involved in the autophagic machinery. Our brief study reports for the first time evidence of decreased cardiac autophagic levels in diabetic patients.
Keywords: autophagy; heart; type 2 diabetes